2004
DOI: 10.1002/art.20042
|View full text |Cite
|
Sign up to set email alerts
|

Family study of fibromyalgia

Abstract: Objective. To assess for familial aggregation of fibromyalgia (FM) and measures of tenderness and pain, and for familial coaggregation of FM and major mood disorder (major depressive disorder or bipolar disorder).Methods. Probands meeting the American College of Rheumatology criteria for FM and control probands with rheumatoid arthritis (RA) and no lifetime diagnosis of FM were recruited from consecutive referrals to 2 community-based rheumatology practices. Probands were ages 40-55 years and had at least 1 fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
227
1
19

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(257 citation statements)
references
References 41 publications
(47 reference statements)
10
227
1
19
Order By: Relevance
“…Gathering data from multiple sources is therefore highly desirable when assessing children and adolescents with chronic pain. The findings of the present study, which used an unusually precise matched control group design, confirmed the results of past research indicating that mood difficulties and pain sensitivity tend to cluster in families (8), and that parents of adolescents with JPFS have a higher likelihood of experiencing chronic pain themselves (12). Mothers of adolescents with JPFS in this study reported significantly greater depressive symptoms than mothers of comparison peers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Gathering data from multiple sources is therefore highly desirable when assessing children and adolescents with chronic pain. The findings of the present study, which used an unusually precise matched control group design, confirmed the results of past research indicating that mood difficulties and pain sensitivity tend to cluster in families (8), and that parents of adolescents with JPFS have a higher likelihood of experiencing chronic pain themselves (12). Mothers of adolescents with JPFS in this study reported significantly greater depressive symptoms than mothers of comparison peers.…”
Section: Discussionsupporting
confidence: 88%
“…Items are rated on a 5-point Likert scale regarding the degree to which each symptom distressed the individual in the past week (0 ϭ not at all, 4 ϭ extremely). Scores on the anxiety and depression subscales were used in this study based upon past research indicating a higher prevalence of anxiety and mood symptoms in fibromyalgia patients and family members (8). The SCL-90-R has demonstrated adequate reliability (28) and has been previously used to assess distress in parents of children with chronic illness (29,30).…”
Section: Adolescent Functioningmentioning
confidence: 99%
“…Similarly, studies of FM have demonstrated a familial or genetic influence. For example, a high prevalence of FM has been found repeatedly among offspring of mothers with FM, and relatives of people with FM have a lower tender point threshold than the general population (Arnold et al 2004;Buskila et al 1996). Another study showed that husbands of women with FM had a high prevalence of FM .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both PTSD and FM are thought to be partially heritable. Family studies have shown that FM aggregates strongly in families (Arnold et al 2004;Buskila and Neumann 1997;Buskila et al 1996;Pellegrino et al 1989), but linkage studies have found either a weak linkage or none at all (Gursoy 2002;Yunus et al 1999). Investigations into the heritability of PTSD have shown that PTSD is related to family history of psychiatric illness (Davidson et al 1989;Koenen et al 2002;Koenen et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Ratings of global change have been used in both intervention and methodological studies. [35][36][37][38] A single question was used post-intervention, which asked participants how they felt in terms of their general well-being and health compared with pre-intervention using a seven-point scale: very much worse, worse, somewhat worse, the same, somewhat better, better, or very much better.…”
Section: Secondary Outcome Measuresmentioning
confidence: 99%